The basic directions of the accomplishment of preparatory conception of future teachers in modernization of education - Sultanov Mukhtor Mamadalievich; Dzhumaev Mamanazar Irgashevich (Technium Social Sciences Journal, 2020)
Over the past thirty years, many reforms have been carried out in the education of intellectually, physically perfect youth. Mathematics is identified as one of the priority areas for the development of science in our country in 2020. Over the past period, a number of systematic works have been carried out aimed at raising mathematical science to a qualitatively new level. In order to further improve the system of teaching mathematical science at all levels of education, to support the effective work of teachers, to expand the scale and practical importance of scientific research, strengthen ties with the international community, and also fulfill the tasks identified in the State Program for the Implementation of the Five-Step Action Strategy priority areas of development of the Republic of Uzbekistan in 2017 - 2021 in the "Year of the development of science, education and the digital economy".